Pattern of chromosomal aberrations in primary liver cancers identified by comparative genomic hybridization - Homayounfar, Kia; Gunawan, Bastian; Cameron, Silke; Haller, Florian; Baumhoer, Daniel; Uecker, Stefan; Sander, Bjoern; Ramadori, Giuliano; Lorf, Thomas; Füzesi, László (Human Pathology, 2009)
Little is known about the molecular cytogenetic changes in cholangiocarcinoma and combined hepatocellular-cholangiocarcinoma, and on the prognostic significance of chromosomal imbalances in hepatocellular carcinoma. Seventy-eight cases of primary liver cancer with available median follow-up of 16.5 months, including 49 hepatocellular carcinomas, 22 cholangiocarcinomas, and 7 combined hepatocellular-cholangiocarcinomas, were examined by comparative genomic hybridization. In hepatocellular carcinoma, the most frequent changes were +8q (54%), -8p (54%), and +1q (42%), followed by -6q (35%), -4q (33%), -13q (29%), -14q (25%), -16q (19%), -17p (19%), +17q (17%), and +20q (15%). In comparison, cholangiocarcinoma had more gains, losses, and breakpoints than hepatocellular carcinoma or combined hepatocellular-cholangiocarcinoma, specifically more frequently -6q (91%), -3p (68%), -9p (55%), -14q (55%), -13q (45%), +1q (41%), +7q (36%), +7p (32%), and +8q (32%). Combined losses at 6q and 3p appeared to be highly characteristic for cholangiocarcinoma. In contrast, combined hepatocellular-cholangiocarcinoma shared frequent +1q (71%), +8q (57%), and -8p (57%) with hepatocellular carcinoma, but a tendency for higher numbers of imbalances with cholangiocarcinoma. Overall, higher numbers of changes, breakpoints, or gains appeared to carry unfavorable prognostic value among hepatocellular carcinomas, with higher numbers of gains retaining prognostic value among R0-resected hepatocellular carcinomas. Cholangiocarcinoma is characterized by combined losses at 6q and 3p and a tendency for chromosomal instability. On the other hand, combined hepatocellular-cholangiocarcinoma may share similar chromosomal changes with both hepatocellular carcinoma and cholangiocarcinoma, as reflected by common hepatocellular carcinoma-like +8q, +1q, and -8p and a tendency for cholangiocarcinoma-like chromosomal instability. In hepatocellular carcinoma, higher number of gains may prove an adverse prognostic parameter. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2025-03-24
Keywords: Cholangiocarcinoma; Comparative genomic hybridization; Hepatocellular carcinoma; Prognostication